(untitled) (Research, Society and Development, 2021)
Through public policies, women gained more space and freedom within the context of Brazilian health and legal rights. Their rights, however, are not always respected. With this, the objective is to identify which laws are in force in Brazilian territory and documents from the Ministry of Health that ensure the rights of pregnant women, parturients and postpartum women. This is a document review where a survey of documents from the Ministry of Health and current national legislation was carried out to determine which rights are guaranteed by laws for pregnant and postpartum women, through the websites of the Federal Government. 34 laws, ordinances, programs and policies were listed. Thus, it was possible to relate to public policies that ensure health care, labor and social rights during the pregnancy-puerperal period, as well as the rights for the newborn, in addition to observing several flaws in the legislation, especially with regard to paternity leave. With this, it is expected to cooperate with foundation strategies for women in the pregnancy and puerperal period and for health professionals in the health education process.